2019
DOI: 10.1039/c8ra07926a
|View full text |Cite
|
Sign up to set email alerts
|

Scope of organometallic compounds based on transition metal-arene systems as anticancer agents: starting from the classical paradigm to targeting multiple strategies

Abstract: The advent of the clinically approved drug cisplatin started a new era in the design of metallodrugs for cancer chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 244 publications
(210 reference statements)
0
47
0
Order By: Relevance
“…This opened the door for the development of a myriad of organometallic complexes bearing the half-sandwich ruthenium(II)-arene scaffold [ 53 , 54 ]. Among those, symmetric and mixed cationic trithiolato-bridged dinuclear ruthenium(II)-arene compounds of general formula [( η 6 - p -MeC 6 H 4 Pr i ) 2 Ru 2 ( µ 2 -SR) 3 ] + [ 55 , 56 ] and, respectively, [( η 6 - p -MeC 6 H 4 Pr i ) 2 Ru 2 ( µ 2 -SR 1 )( µ 2 -SR 2 ) 2 ] + [ 57 ] ( Figure 1 ) have shown high cytotoxicity against human cancer cells (IC 50 values as low as 30 nM against A2780 human ovarian cancer cells and the cisplatin-resistant variant A2780cisR) [ 58 ].…”
Section: Introductionmentioning
confidence: 99%
“…This opened the door for the development of a myriad of organometallic complexes bearing the half-sandwich ruthenium(II)-arene scaffold [ 53 , 54 ]. Among those, symmetric and mixed cationic trithiolato-bridged dinuclear ruthenium(II)-arene compounds of general formula [( η 6 - p -MeC 6 H 4 Pr i ) 2 Ru 2 ( µ 2 -SR) 3 ] + [ 55 , 56 ] and, respectively, [( η 6 - p -MeC 6 H 4 Pr i ) 2 Ru 2 ( µ 2 -SR 1 )( µ 2 -SR 2 ) 2 ] + [ 57 ] ( Figure 1 ) have shown high cytotoxicity against human cancer cells (IC 50 values as low as 30 nM against A2780 human ovarian cancer cells and the cisplatin-resistant variant A2780cisR) [ 58 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the realm of bio‐organometallic chemistry, the ferrocifen system continues to attract significant attention . These molecules possess a ferrocenyl‐ene‐ p ‐phenol motif, and a basic dimethylaminoalkoxy chain, as in 3 .…”
Section: Introductionmentioning
confidence: 99%
“…This compound inspired the development of subsequent small molecule metal complexes as anticancer drugs. Because of this breakthrough, researchers have considered whether other metal complexes have anticancer effects . In 1972, Brown found that Ph 3 SnOOCCH 3 can inhibit the growth of mouse tumors, and scientists have reported the in vitro anticancer activity of organotin compounds .…”
Section: Introductionmentioning
confidence: 99%
“…Because of this breakthrough, researchers have considered whether other metal complexes have anticancer effects. [2][3][4][5][6][7] In 1972, Brown [8] found that Ph 3 SnOOCCH 3 can inhibit the growth of mouse tumors, and scientists have reported the in vitro anticancer activity of organotin compounds. [9][10][11][12][13] After extensive research, organotin complexes are considered a promising class of anticancer drug.…”
mentioning
confidence: 99%